Efficiency of polyaluminum nitrate sulfate–polyamine hybrid coagulants for silica removal. Issue 38 (14th August 2016) - Latour, Isabel; Miranda, Ruben; Carceller, Rosa; Blanco, Angeles
Abstract: Previous studies have demonstrated the efficiency of commercial polyaluminum–polyamine coagulants for high silica removal from industrial effluents without pH adjustment. This paper studies the efficiency of newly developed tailor-made hybrid coagulants for silica removal, based on the combination of a commercial polyaluminum nitrate sulfate (PANS) and three polyamines (PAs) of different molecular weights. Four hybrids for each polymer, with different proportions of PANS and polyamine (5, 10, 15, and 20%) were tested at two initial pHs (8.4 and 10.5) and five dosages (in the range 500–2, 500 mg/L). Results showed that without pH regulation (pH 8.4), all the hybrids were more efficient than PANS on silica removal, 5% of polyamine being the optimum content (>50 vs. 30% silica removal obtained by PANS). For the same level of efficiency (30% silica removal), the required dosages of hybrids are considerably lower than for PANS: 500 vs. 2, 500 mg/L. At initial pH of 10.5, higher silica removal rates are obtained (90%) with all the products and the differences in efficiency between hybrid coagulants and PANS were minor. The hybrid coagulants were always more efficient in COD removal: 51 vs. 37% at initial pH 8.4, and especially at initial pH 10.5 (for similar silica removal): 31 vs. 4%. The effect of molecular weight of the PAs was significant for COD removal (higher molecular weight PAs are more efficient for COD removal), while it was not significant for silica removal efficiency. The main flocculation mechanisms and the visual aspect of the flocs for the different treatments have been analyzed. It is concluded that PANS induced a sweep flocculation, while PA hybrids produced flocculation by a combination of sweep flocculation and patch formation.